PSIII-2 Are There Attitudinal Differences Between Male and Female Mexican Swine Caretakers Toward Euthanasia?. (12th April 2022) - Yarian, Jacob; Stalder, Kenneth J; Arruda, Andréia; Ross, Jason W; Skaar, Brad; Pairis-Garcia, Monique; Jass, Cassandra; Millman, Suzanne; Robles, Ivelisse; Johnson, Anna K
Abstract: Hispanic and Latino workers represent a growing sector of the swine industry, yet their attitudes on euthanasia remain unclear. The objective was to investigate how euthanasia attitudes differ between male and female Mexican TN visa caretakers. A total of 32 (16 male and 16 female) caretakers from a single swine company were enrolled. All completed a 31-question online survey in Spanish. Demographic questions included age, sex, highest educational degree earned, and euthanasia experience. Non-demographic questions were ranked on a 5-point Likert scale (1 = Strongly Disagree to 5 = Strongly Agree). Questions were categorized into 4 groups (a) confidence defined as knowing a pig is unlikely to recover, and can identify what is wrong (b) knowledge defined as having the skills to care for a ill or injured pig before euthanasia, and knowing how to complete euthanasia (c) decision defined as their thought process that results in a timely euthanasia treatment option and, (d) comfort defined as their feelings towards conducting euthanasia and how they cope afterwards. Furthermore, questions were delineated into adult pig and piglet. Caretaker mean average age was 32 yr (range 24 to 53 yr), and 99% had received a higher education, with 63% never euthanizing an animal prior to working with pigs. Median caretaker responses indicated that they were confident for both pigs and piglets (Male 4.25; Female 4.13), had knowledge (Male 3.34; Female 3.17), could make timely euthanasia decisions (Male 3.33; Female 3.33) and were comfortable performing and coping with euthanasia (Male 3.08 pigs/3.14 piglets; Female 3.17 pigs/3.40 piglets). In conclusion, for Mexican TN visa holders, being male or female does not affect their attitude towards euthanasia, which was positive. This is encouraging because their actions will support swine welfare.